(untitled) (Applied Biological Research, 2023)
The aim of this study was to isolate novel mosquitocidal bacteria from clayey soil. The soil samples were collected during the period 2021 to 2022 from an agricultural field of Tamil Nadu (India). The samples were processed for isolating the bacteria on nutrient yeast extract salt medium. The bacterial cell mass was harvested after 72 h of lyophilisation. Bioassay was carried out with the bacterium against larval species of Culex quinquefasciatus, Aedes aegypti and Anopheles stephensi. Whole genome sequence (WGS) analysis (Illumina) was done to identify the strain. Growth dynamics, biochemical characteristics, and toxicity assays with non-target aquatic organisms were also done. Based onWGS analysis the new isolate was identified as Bacillus thuringiensis serovar israelensis. The strain was coded as VCRC-B651. The isolate exhibited effective toxicity against A. aegypti, A.stephensi, and C. quinquefasciatus with LC50 values of 0.005, 0.009 and 0.009 mg L-1, respectively, and LC90 values of 0.009, 0.02 and 0.018 mg L-1, respectively. The isolate exhibited higher mosquitocidal activity as compared to the WHO reference strain (Bti H14). No adverse effect on aquatic non-target organisms was observed. The new isolate was highly efficacious in controlling the mosquito larvae.